Determinants of choice of birth place among women in rural communities of southwestern Nigeria - Love Bukola Ayamolowo; Titilayo Dorothy Odetola; Sunday Joseph Ayamolowo (Elsevier, 2020)
Background: Choice of birth place remains a significant risk factor for maternal mortality in rural communities. Despite national efforts of increasing availability of maternal healthcare services, rural women across Africa still under-utilize the services. This study assessed the determinants of choice of birth places among childbearing women in rural communities. Methods: This descriptive community-based cross sectional study employed a convergent parallel mixed methods research design. It involved childbearing age (15 to 49 years) women who gave birth within five years prior to the study. Respondents were selected by multistage sampling technique. Data collection was by pre-tested, structured, interviewer-administered questionnaires and Focus Group Discussion (FGD) guide. Of the 410 questionnaires administered, 403 were suitable for analysis giving a response rate of 98.3%. Questionnaires and FGD data were analyzed using STATA version 14 and software ATLAS.ti version 7.5.10, respectively. Alpha was set at 5%. The study was approved by the Health Research Ethics Committee of Obafemi Awolowo University, Nigeria (IPHOAU/12/873). Results: Only 38% of the respondents had institutional delivery. Among others, distance, providers' approach, inadequate healthcare facilities and personnel were identified as determinants of choice for childbirth place. Parity and age were not significantly associated with birth place (p > 0.05). Conclusion: Determinants of non-institutional birth found in this study majorly include maternal educational status, distance of health facilities and providers' approach. These have useful implications for both health providers and health policy makers for improving and strengthening institutional births strategies in rural Nigeria.